Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1007/s44297-023-00008-7
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the functional study of host resistance-related genes against Heterodera glycines

Long He,
Nabi Noor Ul Ghani,
Luying Chen
et al.

Abstract: Soybean (Glycine max L.), a crucial crop that provides essential nutrition, is experiencing increasing demand to meet protein and oil requirements. However, the menace of soybean cyst nematode (SCN) disease, caused by Heterodera glycines, poses a substantial threat globally, resulting in significant annual economic losses. While cultivating resistant varieties is an eco-friendly approach to control SCN, the excessive use of a single variety triggers ongoing evolution of SCN races, jeopardizing the soybean indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…The current study revealed the association of stress resistance in ancient bayberry with plant microbial communities, which provides a new perspective to study the interaction between plants and pathogens/insects (He et al, 2023;Liu et al, 2023;Tao et al, 2023). The plant microbiome refers to the enormous variety of microorganisms that live in close proximity to plants in the rhizosphere, endosphere, and other compartments such as leaf surfaces, pollen, and nectar (Liu et al, 2017, Liu andBrettell, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…The current study revealed the association of stress resistance in ancient bayberry with plant microbial communities, which provides a new perspective to study the interaction between plants and pathogens/insects (He et al, 2023;Liu et al, 2023;Tao et al, 2023). The plant microbiome refers to the enormous variety of microorganisms that live in close proximity to plants in the rhizosphere, endosphere, and other compartments such as leaf surfaces, pollen, and nectar (Liu et al, 2017, Liu andBrettell, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…The soybean cyst nematode (SCN) is recognized as a significant global threat to soybean production [ 4 , 24 ]. Notably, our analysis revealed that 38.35% (28 out of 73) of the identified GmSCPL genes are located within regions corresponding to known SCN-related quantitative trait loci (QTLs), as shown in Figure S1 and Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…The distribution pa ern of SCPL genes across the chromosomes does not exhibit a strong correlation with gene density, GC content, or GC skew (Figure 3). The soybean cyst nematode (SCN) is recognized as a significant global threat to soybean production [4,24]. Notably, our analysis revealed that 38.35% (28 out of 73) of the identified GmSCPL genes are located within regions corresponding to known SCN-related quantitative trait loci (QTLs), as shown in Figure S1 and Table S2.…”
Section: Chromosomal Distribution and Gene Duplication Of The Gmscpl ...mentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have consistently shown a clear relationship between the abundance and diversity of soil microbes and the occurrence of soil-borne diseases ( Jia et al, 2023 ). The soil microbial community structure and composition plays a critical role in maintaining ecosystem resilience and sustainability, including the suppression of pathogens ( Wagg et al, 2014 ), which expanded traditional plant pathogen interaction research ( He et al, 2023 ; Liu et al, 2023 ; Tao et al, 2023 ). In recent years, high-throughput sequencing technology has emerged as a powerful tool for rapidly and accurately assessing the diversity and composition of microbial communities in diverse sample types.…”
Section: Introductionmentioning
confidence: 99%